The International Endometriosis Evaluation Program (IEEP Study) – A Systematic Study for Physicians, Researchers and Patients - Burghaus, S.; Fehm, T.; Fasching, P. A.; Blum, S.; Renner, S. K.; Baier, F.; Brodkorb, T.; Fahlbusch, C.; Findeklee, S.; Häberle, L.; Heusinger, K.; Hildebrandt, T.; Lermann, J.; Strahl, O.; Tchartchian, G.; Bojahr, B.; Porn, A.; Fleisch, M.; Reicke, S.; Füger, T.; Hartung, C.-P.; Hackl, J.; Beckmann, M. W.; Renner, S. P. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Endometriosis is a heterogeneous disease characterized by a range of different presentations. It is usually diagnosed when patients present with pain and/or infertility, but it has also been diagnosed in asymptomatic patients. Because of the different diagnostic approaches and diverse therapies, time to diagnosis can vary considerably and the definitive diagnosis may be delayed, with some cases not being diagnosed for several years. Endometriosis patients have many unmet needs. A systematic registration and follow-up of endometriosis patients could be useful to obtain an insight into the course of the disease. The validation of biomarkers could contribute to the development of diagnostic and predictive tests which could help select patients for surgical assessment earlier and offer better predictions about patients who might benefit from medical, surgical or other interventions. The aim is also to obtain a better understanding of the etiology, pathogenesis and progression of the disease. Material and Methods: To do this, an online multicenter documentation system was introduced to facilitate the establishment of a prospective multicenter case-control study, the IEEP (International Endometriosis Evaluation Program) study. We report here on the first 696 patients with endometriosis included in the program between June 2013 and June 2015. Results: A documentation system was created, and the structure and course of the study were mapped out with regard to data collection and the collection of biomaterials. Conclusion: The documentation system permits the history and clinical data of patients with endometriosis to be recorded. The IEEP combines this information with biomaterials and uses it for scientific studies. The recorded data can also be used to evaluate clinical quality control measures such as the certification parameters used by the EEL (European Endometriosis League) to assess certified endometriosis centers.
Keywords: endometriosis; biomarker; epidemiology; diagnostics; case control study